Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1590/1982-0275202138e200020
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement in Higher Education, age and parental education level

Abstract: Within the scope of socio-cognitive theories, student engagement in school has been studied as a multidimensional construct. A four-dimensional perspective was adopted, with the dimensions: affective, cognitive, behavioural and agentic. The objective, to analyse how the variables age and parental education relate to student engagement in school. The sample consisted of 715 Portuguese public Higher Education students from the Lisbon area. The data was collected through an online survey, which included the Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…Sin embargo, esto podría producir un desgaste físico y mental, debido a que en los últimos años de estudio los estudiantes de Enfermería tienen que afrontar sus prácticas preprofesionales y el desarrollo de sus trabajos de investigación (Tesis) para poder obtener su grado de bachiller y título profesional. Un resultado parecido se reporta en Portugal, donde se evaluó el CA de 715 estudiantes universitarios y concluyeron que quienes tenían más de 25 años se comprometían más con sus estudios, ya que habían construido un sentido de pertenencia e identidad con mayor conciencia y habían consolidado su orientación profesional (31).…”
Section: Discussionunclassified
“…Sin embargo, esto podría producir un desgaste físico y mental, debido a que en los últimos años de estudio los estudiantes de Enfermería tienen que afrontar sus prácticas preprofesionales y el desarrollo de sus trabajos de investigación (Tesis) para poder obtener su grado de bachiller y título profesional. Un resultado parecido se reporta en Portugal, donde se evaluó el CA de 715 estudiantes universitarios y concluyeron que quienes tenían más de 25 años se comprometían más con sus estudios, ya que habían construido un sentido de pertenencia e identidad con mayor conciencia y habían consolidado su orientación profesional (31).…”
Section: Discussionunclassified
“…A second source of evidence comes from the examination of longitudinal trajectories of engagement. Some studies have found job engagement to slightly increase as a function of age among mixed samples of employees (James et al, 2011;Kim & Kang, 2017) and undergraduate students (Covas & Veiga, 2021), whereas others found decreasing trajectories among samples of secondary students followed over the course of their studies (Goñi et al, 2018) or of employees followed for a period of five days (Zuo et al, 2021). Others also reported evidence of stability in engagement levels during the first five weeks following the implementation of an organizational change (van den Heuvel et al, 2020).…”
Section: A Longitudinal Perspective On Engagementmentioning
confidence: 99%